Flow past a rectangular cylinder close to a free surface. (15th August 2019) - Zhong, Wenjie; Deng, Lu; Xiao, Zhiying
Abstract: Flow past rectangular cylinders represents an idealized flow around bluff bodies. Knowing the hydrodynamic properties of rectangular cylinders in a steady flow is of practical importance for many engineering applications. Although the unbounded flow past rectangular cylinders has been broadly studied, investigations on the flow around rectangular cylinders close to the free surface are limited. In the present study, two-dimensional multiphase simulations of flow past rectangular cylinders were conducted using RANS. The Mentor shear stress transport (SST) k - ω model and the volume of fluid (VoF) model were adopted. The Mentor SST k - ω model is capable of accurately predicting the flow past rectangular cylinders near the free surface when the width-to-length ratio is larger than 0.7. The effect of the depth-to-length ratio on the hydrodynamic properties of rectangular cylinders is affected by the width-to-length ratio and becomes significant when the depth-to-length ratio is lower than 1.0. The effect of the width-to-length ratio on the flow past rectangular cylinders near the free surface is different from that in an infinite domain. The findings from the present study can provide a deep understanding of the hydrodynamic properties of rectangular cylinders close to the free surface. Highlights: Multiphase simulations with the Mentor SST k - w model can provide reasonable predictions of the flow around rectangular cylinders near a free surface when w / l ≥ 0.7. The effect of d / l on the flow around rectangular cylinders is affected by w / l . Variations of the force coefficients with d / l are similar for rectangular cylinders with the w / l ratios of 1.0 and 3.0, but the amplitudes of variation and the corresponding ranges of d / l are different. The free surface effects on the flow past rectangular cylinders become significant when d / l ≤ 1.0. The substantial flow change occurs at around d / l = 0.6 and d / l = 0.9 for rectangular cylinders with the w / l ratios of 1.0 and 3.0, respectively. There exists a critical d / l for rectangular cylinders located near a free surface. The critical d / l is related to the w / l ratio of rectangular cylinders. The effect of w / l on the flow past rectangular cylinders close to a free surface is different from that in an infinite domain due to the approaching of the surface.